Fabrication and characterization of gold ultra and microelectrodes - Menolasina, Sabino (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Gold disk ultramicroelectrodes of 10 μm and microelectrodes of 60 μm diameter were fabricated using gold wires. These ultra and microelectrodes were characterized by electrochemical measurements and using scanning electron microscopy (SEM) for determining the real shape of the surface, and obtaining information about the quality of the seal at the electrode material-insulating material interface.